THE USES OF CLAUSE RELATIONS IN THE GUARDIAN ARTICLE: DESTROYING THE WORLD'S NATURAL HERITAGE: ‘KOMODO IS REACHING A TIPPING POINT’ - Elma Pravitha Dewi; Acep Haryudin (PROJECT (Professional Journal of English Education), 2019)
The aim of this paper was to know type of clause relations used in The Guardian Article and to find out the dominant type of clause relation, entitled Destroying the world's natural heritage: 'Komodo is Reaching a Tipping Point'. The researcher using the data from online newspaper with qualitative method and descriptive analysis. The researcher uses Winter theory in 1977 to analysis type of clause relations. The result shows that there are two types of clause relations that used in The Guardian Article, there are Matching Relation & Logical Sequence Relation with some sub-types. The most dominant type that found in The Guardian Article is Cause-Consequence. Keywords:  Clause Relation, Online News, Discourse